Strategi Promosi Hotel melalui Wisata Syariah dalam Meningkatkan Kualitas Pelayanan Jasa - Suhendra Atmaja; Poppy Ruliana (Inter Komunika, 2017)
Abstract. Sari Ater Hotel & Resort is located area Ciater Subang Regency is a company entrusted by the Municipal Government to manage the natural attractions of hot water Ciater promotion strategy based travel sharia done by far is direct (direct promotion) and indirectly (indirect promotion) addressed to the consumers / travelers to encourage the achievement of promotional services, companies need to provide additional services (supplement service) on transactions core services (core services) so that core services can provide satisfaction, additional services may be reflected in the mix elements of service offered Sari Ater Hotel & Resort to the visitors / tourists. The problem is how do promotional strategies Sari Ater Hotel & Resort through sharia travel in improving the quality of service. The purpose of this study is to analyze the mengetahuai and promotional strategies Sari Ater Hotel & Resort through sharia travel in improving the quality of service to the tourists. The concept of promotion strategies in this study refers to the opinion of Philip Kotler (2002) who argued that in order to effectively promote the need for the promotion mix, which is the optimal combination for any kind of events or the selection of the most effective promotional activities to increase sales. There are four types of promotional activities, among others: advertising, personal selling, sales promotion, public relations and direct promotion. The method used is descriptive qualitative, key informants and informant in this research is Marketing Manager Sari Ater Hotel & Resort, Public Relations Manager Sari Ater Hotel & Resort, Front Liner, F & B Manager Sari Ater Hotel & Resort and the few tourists who come visit. Data was collected through several stages, observation, interview, documentation and triangulation. Data analysis technique is done through data reduction, display, verification / conclusion (Miles & Huberman). The results showed that of the four starategi sale Sari Ater Hotel & Resort through sharia travel tend to do personal selling, sales promotion and direct dam for the promotion, while the public relations strategy to do more personal approach was persuasive, so as to form the image and reputation. All four of these strategies can actually improve the quality of service the hotel proved to the many tourists who come both from domestic and from abroad, including from Japan, Saudi Arabia, Singapore and Malaysia.Keywords : Communication, Promotion Strategy, Quality of Service